Application Of Problem Based Learning (PBL) Model To Increase Students ’ Learning Motivation In The Material of Life Diversity Class X SMA Muhammadiyah 1 Gresik - Muttaqin, Ainul (Proceeding International Conference on Lesson Study, 2023)
The phenomenon of declining student motivation, especially after the Covid-19 pandemic, is a prominent problem. Students experience a transition from distance learning coupled with the absence of social interaction for a long time. The expected goal is to determine the increase in student learning motivation through problem based learning (PBL) learning models and high-level thinking skills of students. This research was carried out at SMA Muhammadiyah 1 Gresik in September 2022. The method used is to use the observation of learning activities. From the results of the study it can be concluded that (1) most students can understand the concept of diversity of living things by using PBL learning model. (2) The attitude shown by students as a whole has been in the form of critical reasoning, cooperation, and independence. (3) in the learning process, students are able to demonstrate skills in independently compiling tables on plant diversity at the level of genes and species in schools, planning actions and choosing the right plants. (4) PBL learning Model with TPACK approach is felt very happy by students because they can learn to use devices, can learn to solve problems, and have experience through observation activities.